2013
DOI: 10.3390/ijms140816986
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Alpha-L-Fucosidase Gene FUCA1 in Human Colorectal Tumors

Abstract: In previous studies we described a decreased alpha-l-fucosidase activity in colorectal tumors, appearing as a prognostic factor of tumoral recurrence. The aim of this work was to extend the knowledge about tissue alpha-l-fucosidase in colorectal cancer by quantifying the expression of its encoding gene FUCA1 in tumors and healthy mucosa. FUCA1 mRNA levels were measured by RT-qPCR in paired tumor and normal mucosa tissues from 31 patients. For the accuracy of the RT-qPCR results, five candidate reference genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
3
29
0
2
Order By: Relevance
“…Although we have restricted our subject to the enzymes of O -glycan biosynthesis, the actions of glycosidases, which are involved in O -glycan degradation, may have an important regulatory role. For example, it is known that α - l -fucosidase (EC 3.2.1.51) is downregulated in certain types of colorectal cancer [ 79 ], from which we infer that an increase in Lewis-type epitopes might be the result of both increased fucosyltransferase activity in Golgi and decreased fucosidase activity in either tissue or plasma. In the future, therefore, this model could be extended to include enzymes involved in the catabolism of O-linked glycoproteins.…”
Section: Discussionmentioning
confidence: 89%
“…Although we have restricted our subject to the enzymes of O -glycan biosynthesis, the actions of glycosidases, which are involved in O -glycan degradation, may have an important regulatory role. For example, it is known that α - l -fucosidase (EC 3.2.1.51) is downregulated in certain types of colorectal cancer [ 79 ], from which we infer that an increase in Lewis-type epitopes might be the result of both increased fucosyltransferase activity in Golgi and decreased fucosidase activity in either tissue or plasma. In the future, therefore, this model could be extended to include enzymes involved in the catabolism of O-linked glycoproteins.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, FUCA1 expression is significantly reduced in cancers of the large intestine, and low FUCA1 expression is related to poorer prognosis in patients with cancer of the large intestine or breast. It has previously been reported that FUCA1 mRNA expression is decreased in colorectal cancers . In addition, it was reported that fucosylation promotes cancer development and malignant progression in breast cancers .…”
Section: Discussionmentioning
confidence: 96%
“…It has previously been reported that FUCA1 mRNA expression is decreased in colorectal cancers. (37) In addition, it was reported that fucosylation promotes cancer development and malignant progression in breast cancers. (38) These reports are in agreement with our results, and suggest that FUCA1 may have tumor-suppressive activity, and could be a therapeutic target in the treatment of cancers in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to anaplastic thyroid cancer, FUCA1 expression is downregulated in aggressive forms of colorectal cancers (26), breast cancers (27), and neuroblastomas (28). It should be noted that a gradual decrease in FUCA1 expression was observed with progression of disease from earlier to advanced stages in colorectal cancer (26). Also in the case of thyroid cancer, as shown previously (25) less aggressive thyroid PTCs expressed higher levels of FUCA1, compared with the more aggressive ATCs, which displayed lower levels of FUCA1 expression.…”
Section: Fuca1 Is Transcriptionally Induced By P53mentioning
confidence: 99%